Pengaruh Faktor Eksternal Terhadap Nilai Perusahaan (PBV) dan Harga Saham Terhadap Perusahaan Manufaktur di Bursa Efek Indonesia - Ni Putu Santi Suryantini; I Wayan Edi Arsawan (Faculty of Economics and Business Udayana University, 2014)
The aims of this research i s to examine the influence of external factors on f irm value, the effect of companyvalue on stock price, and influence of external factors on stock price. The samples were 30 manufacturingcompanies li sted in Indonesia Stock Exchange through pusposive sampling. This study applied secondarydata based on documentation of the companies. Data analysis was performed by using Smart PLS. Out of thethree indicators of external factors, two of them i.e. inflation and exchange rate, met the criterion, becausethey have loading factor above 0,5 . The resul ts show that, external factors negatively effect firm value withcoefficient value of 0.0933, means that i f external factors changes, company’ s value thr ough PBV , movetowar d negative di r ection. V alue of company influence stock price positively with coeff icient value of 0.0637.Additionally, external factors show negat ive effect on stock price with coefficient value of 0.1019, as anindication that the changes of external factor has negative impl ication to the stock price